Microbiology and resistance in first episodes of spontaneous bacterial peritonitis: implications for management and prognosis. Issue 6 (June 2016) - Friedrich, Kilian; Nüssle, Simone; Rehlen, Tobias; Stremmel, Wolfgang; Mischnik, Alexander; Eisenbach, Christoph
Abstract: Purpose: International guidelines for antibiotic treatment of spontaneous bacterial peritonitis (SBP) are based on studies conducted decades ago and do not reflect regional differences of bacterial epidemiology. Methods: We retrospectively analyzed epidemiology of agents, antibiotic resistance patterns, and survival in liver cirrhosis patients with their first episode of SBP during the years 2007–2013. Results: Of the 311 patients included, 114 patients had a positive ascites culture, and 197 had an ascitic neutrophil count >250 μL. Gram‐positive bacteria (47.8%) were more frequently found than Gram‐negatives (44.9%), fungi in 7.2%. Enterobacter spp. (40.6%), Enterococcus spp. (26.1%), and Staphylcoccus spp. (13.8%) were the most frequently isolated agents. Third‐generation cephalosporins covered 70.2% of non‐nosocomial and 56.3% of nosocomial‐acquired SBP cases.When SBP was diagnosed by a positive ascitic culture, survival was highly significantly reduced (mean: 13.9 ± 2.9 months; 95% confidence interval [CI]: 8.1–19.8) compared with culture‐negative SBP patients (mean: 44.1 ± 5.4 months; 95% CI: 33.4–54.9; P = 0.000). Along with model of end‐stage liver disease score and intensive care unit contact, a positive ascites culture remained an independent risk factor associated with poor survival (odds ratio: 1.49; 95% CI: 1.09–2.03) in multivariate analysis; piperacillin/tazobactam proved to be an adequate antibiotic for nosocomial and non‐nosocomial SBP in 85.1% and 92.5%, respectively. SBP infection with Enterococcus spp. was associated with poor patient survival ( P = 0.048). Conclusions: Third‐generation cephalosporins have poor microbial coverage for treatment of SBP. Current guidelines need to adapt for the emerging number of Gram‐positive infectious agents in SBP patients.